(3JYde cja JSJKeQ THcI GdGfJQfjJ dJaYjd h GfLGM TQcJc GdUZjQIs - (3GfWhGf Gh(B, (3dGfJfjGfs; (3SYjO GdMSjfI eQcR GdJYQjH h GdHQeLI(B, s ((3dHfGf(B:s (3GdOGQ GdYQHjI ddYdhe fGTQhf(B,s, 2009)
(3GHJcGQ GSJQGJjLjI GfJQfjJ aYGdI , JfXje ESe GdTQcI h MSGH GdHQjO GdGdcJQhfj h ehbY Ydi GdTHcI h GdTQhY aj YedjI GdHjY , JShjb ehbY GdTQcI , JCSjS GdWQa GdNaj ddTQcI aj GdTHcI , LYd GdTQcI CcKQ aYGdjI eY GdGfJQfjJ , GSJQGJjLjGJ GdTQcGJ GdUZjQI Ydi GdGfJQfjJs
Keywords: (3GdCfJQfJs; (3GdJLGQIs; (3GdJLGQI(B- (3GdJcfhdhLjGs; (3GdTQcGJs